Rice sprouts exert immunostimulatory activity in mouse macrophages, RAW264.7 cells - Na Gyeong Geum; Joo Ho Yeo; Ju Hyeong Yu; Min Yeong Choi; Jae Won Lee; Jueng Kyu Baek; Jin Boo Jeong (Food and Agricultural Immunology, 2021)
Rice sprouts are reported to have potential as a functional food agent for health promotion, but studies on the biological activity of rice sprouts are insufficient. Thus, in this study, we investigated whether WERS exhibits immunostimulatory activity in macrophages. WERS increased the production of immunomodulatory factors such as nitric oxide (NO), inducible nitric oxide synthase (iNOS), interleukin-1β (IL-1β), interleukin-6 (IL-6) and tumour necrosis factor-α (TNF-α) in RAW264.7 cells. In addition, WERS activated the phagocytosis of RAW264.7 cells. The inhibition of toll-like receptor 2 (TLR2) and toll-like receptor 4 (TLR4) blocked WERS-mediated production of immunomodulatory factors in RAW264.7 cells. In addition, the inhibition of p38 and JNK suppressed the production of immunomodulatory factors by WERS, and the activation of p38 and JNK was blocked by the inhibition of TLR2 and TLR4. Taken together, WERS induced macrophage activation through TLR2/4-dependent activation of p38 and JNK.